Трансформація менеджменту - Лінькова, Олена Юріївна (Київський національний економічний університет імені Вадима Гетьмана, 2022)
Причини трансформації менеджменту: глобалізація, розвиток ринкової інфраструктури; дифузія інновацій; діджиталізація; зміна соціальних систем. Напрямки розвитку менеджменту: вмотивованість працюючих; командна робота; підвищення відповідальності працівників; управління інноваціями; сталий розвиток.

Reasons for management transformation: globalization, development of market infrastructure; diffusion of innovations; digitalization; change of social systems. Directions of management development: motivation of employees; team work; increasing the responsibility of employees; innovation management; Sustainability.
Management transformation
Keywords: менеджмент; підривні технології; мотивація; соціальний захист; цінності; management; subversive technologies; motivation; the social protection; values